Penyusunan Laporan Laba Rugi Untuk Usaha Mikro Kecil dan Menengah (UMKM) Mie Ayam Bakso Diyan Berbasis Web - Riza Permata; Rasidin Karo Karo Sitepu (PENG: Jurnal Ekonomi dan Manajemen, 2024)
The aim of this research is to design and build a web-based profit and loss statement. Data collection techniques include observations, interviews, literature studies, qualitative descriptive data analysis techniques, and system development methods in the form of SDLC (System Development Life Cycle). The results of the research show that the web system that has been built and the testing process that has been carried out can be used by the owner of the Diyan Bakso Chicken Noodle business to record transactions that occur, capable of displaying general journals, ledgers, trial balances, adjusting journals, work balances and reports. profit and loss. Suggestions that can be given would be to carry out developments in terms of increasing the functionality of the web system by adding, changing and deleting item data, and adding inventory cards automatically.